2017
DOI: 10.21595/jve.2017.17868
|View full text |Cite
|
Sign up to set email alerts
|

Double synchronization states of two exciters with horizontal asymmetric structure in a vibrating system

Abstract: Synchronization of two exciters with asymmetric structure is more widely used in engineering, such as vibrating conveyer, dewatering screen, vibrating screen, however, the synchronization state of two exciters with asymmetric structure in the sub-resonant and super-resonant states is less considered, and it is a valuable research topic. Firstly, we establish a kind of weakly nonlinear vibrating system driven by two exciters with opposite rotation directions and asymmetrical structure. Using Lagrange equations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…where, oxy is the fixed coordinate system, m is the mass of the frame, o is the mass center of the whole vibrating Four springs with the type of ROSTA AB27, (6). Signal acquisition system, (7). Three ROLS remote optical laser sensors, (8).…”
Section: Theoretical Research a Working Principle Of Multi-frequmentioning
confidence: 99%
“…where, oxy is the fixed coordinate system, m is the mass of the frame, o is the mass center of the whole vibrating Four springs with the type of ROSTA AB27, (6). Signal acquisition system, (7). Three ROLS remote optical laser sensors, (8).…”
Section: Theoretical Research a Working Principle Of Multi-frequmentioning
confidence: 99%
“…Djanan et al [16] discussed the influence of the physical characteristics of the motor on the phase difference when two ERs reach the synchronous state. Introducing nonlinear springs, Li et al [17] studied synchronization theory of nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the synchronization theory in the mechanical system has been studied. Recent studies have shown that the vibration system also has double phase synchronization phenomena, which mainly exist in four forms: (1) the bistable phase synchronization phenomenon is natural to appear in some vibration systems with double vibration mass or multimass [8,9], including some rotor-pendulum systems [10,11]; (2) some vibration systems have the in-phase and antiphase synchronization phenomena when they operate in a subresonance or a superresonance state, respectively [12,13]; (3) the event of bistable phase difference intervals also exists in some near-resonance nonlinear vibration synchronous systems [8,10]; (4) it is more popularly known in the vibration synchronization system with two homodromy exciters located at a single vibration mass body [14][15][16], including rotor-pendulum systems [10] and two eccentric rotors with a common rotational axis system [17,18]. e inphase synchronization phenomenon between the two homodromy exciters appears when they are located at a relatively far distance, i.e., the stable phase difference interval is (− 90°, 90°).…”
Section: Introductionmentioning
confidence: 99%